Lelang Jabatan Sebagai Inovasi Dalam Penempatan Aparatur Sipil Negara di Indonesia - Taufik (Universitas Serang Raya, 2020)
The high political intervention of the bureaucracy in this case the placement of the state Civil Apparatus (ASN) has an impact on ASN's inneutrality in the elections involved in practical politics. This is because solely to get the position of positions when the candidate he supported was elected as the head of the district. This article aims to analyze the innovation of the open recruitment policy of ASN. The implementation of high Leadership (JPT) (auction) in Indonesia is generally done well in accordance with merit system, namely based on qualifications, competence, and performance in a fair and reasonable manner with no distinction of political background, race, color, religion, origin, sex, marital status, age, or condition of disability. However, this open recruitment system has not yet decided the chain of political intervention against bureaucracy. The results of the JPT recruitment were handed over to the personnel recruitment officers who were in fact held by political officials. Thus, it is difficult to separate political and administrative dichotomy. In addition, there are still weaknesses in this open recruitment, such as expensive costs, restrictions or (demarcation) of prospective participants of the JPT recruitment, and take a long time. Therefore, this policy needs to be reviewed to not only produce the competent ASN, but also free from political intervention.